Implementation of the COVID-19 Handling Policy in Palu City, Central Sulawesi Province - Ahsan Samad, Muhammad; Ferianto, Fiki; Wulandari, Rina; Panason, Anita (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The Corona Virus Diseases-19 (COVID-19) virus is threatening public health in Palu, Central Sulawesi Province. It is expected that if the local government does not take it seriously, there would be a surge in uncontrolled cases that will surpass the capabilities and capacity of health institutions. The purpose of this research is to examine the execution of Palu City administration policies in dealing with COVID-19. Techniques for gathering data include observation and qualitative questionnaires. Using a case study method, the study focuses on government policy and the events that occur after the policy is implemented, as well as online media outlets. According to the study’s findings, policy execution can be seen in the formation of a strong village, the Nagasi Volunteer team, the Puskesmas’ care in delivery, and the acceleration of vaccination. Overall, the policy’s implementation has gone well; the community and the government have worked together to execute the program.